Content and Citation Analysis of Articles Published in Iranian Journal of Aging, 2006-2015 - Yadollah Abolfathi Momtaz; Ahmad Delbari; Robab Sahaf; Shahla Roustaei; Raziye Sadat Hosseiny; Maryam Ramshini (University of Social Welfare & Rehabilitation Sciences, 2017)
Objectives Scientific journals are one of the most important tools for knowledge transition and translation in the word. Therefore, it is necessary to evaluate these journals with the aim to control the research published in them. The study aimed to conduct a content and citation assessment of articles published in the Iranian Journal of Ageing. Methods & Materials A descriptive bibliometric analysis design was employed in this study. All available manuscripts published from 2006 through 2015 were reviewed. A valid researcher instrument was constructed and employed for data collection. SPSS version 23 was used for analysis. Results Of the 298 published manuscripts, the most common field of publication were physical activity with 18.5%, followed by mental and physical area with 12.4% and 10.4%, respectively. The most popular method used in these published papers (67%) was descriptive-analytic, and the least method (7.1%) was clinical trials. The analysis of the geographical distribution of published papers revealed that the majority of the papers originated from Tehran, but no articles were published from the five provinces of North Khorasan, Kurdistan, Kohgiloyeh and Boyerahmad, Hormozgan, Hamedan. The average of editorial time (speed from submission to publication) was 284 days (SD=143). Approximately 22% of the papers were cited at least once. The mean number of citations per document was 2.26 (SD=1.95). Results of the inferential statistics revealed that research setting and published time were significantly associated with citation.  Conclusion According to the findings from the present study, in order to improve the quantity and quality of the Journal, it is suggested that the editorial board of the Journal take up measures to reduce editorial time. It is also suggested that they should focus on the scope of the Journal and consider appropriate geographical distribution of the published papers.